REALIZATION OF THE SYNERGETIC APPROACH IN THE CONTEXT OF INNOVATIONS IN EDUCATION - Наталя Петрова (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The phenomenon of innovations in the education branch has been analyzed. It has been proved that for the system of specialists' professional training in the education branch the innovation is simultaneously a condition, fundamental, means, form and aim of the pedagogical activity. The extrapolation of the concept "synergy" to the pedagogical reality has been carried out. This contributed to discovering traditions and innovations as complementary components of the educational process. It has been found out, that the realization of the synergistic approach in the context of innovation processes in education contributes to the integrity, systematicity and effectiveness of the pedagogical reality.